Urinoma: a rare complication of ureteral calculi - Gautam, Raj; Shaikh, Tanveer; Attarde, Niket; Gupta, Shitiz; Wani, Jatin; Ghosalkar, Mithilesh Mahesh; Ansari, Sharique; Murali, Sridevi (International Journal of Research in Medical Sciences, 2017)
Urinoma is a collection of extravasated urine either in renal subcapsular or perirenal space. It is caused by obstructive and non-obstructive pathologies. It is rare; with trauma as most common cause in adults and ureteral stones as least common. It mimics symptoms of ureteral stone. CT KUB is best modality to detect it. Here we present a case of ureteral calculi leading to urinomas formation in a 42 years old male patient present with retention of urine and pain in left flank region with nausea, vomiting and fever.